High-efficiency FAPbI3 perovskite thin film and preparation method and application thereof

By adding graphene oxide-polyacrylic acid as grain boundary overseas Chinese crossing agent in the preparation process of FAPbI3 perovskite film, the problems of rough surface and high defect density of the film are solved, and the crystallinity and photovoltaic properties of the film are significantly improved, and the crystallinity and photovoltaic properties of the film are achieved. High efficiency energy conversion efficiency.

CN119521999APending Publication Date: 2025-02-25NANJING TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311078421.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-25
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

There is still room for improvement in the crystallinity, photovoltaic performance and stability of the FAPbI3 perovskite film prepared by traditional methods, mainly due to the rough surface of the film and the high defect density, which affects the carrier transport and energy conversion efficiency.

Method used

By adding graphene oxide-polyacrylic acid as grain boundary overseas Chinese agent to the perovskite precursor solution, ionic recombination and spin coating are carried out to form an efficient FAPbI3 perovskite film. The method includes mixing the perovskite precursor solution with graphene oxide-polypropionic acid solution, stirring evenly at low temperature, spin coating onto a conductive substrate, and depositing the interface modification layer, hole transport layer, metal interpolation layer and metal electrode in turn after annealing. layer.

Benefits of technology

The FAPbI3 perovskite film prepared by this method has excellent crystallinity, flatness and uniformity, which improves the photovoltaic performance and energy conversion efficiency of the device to 23.66%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119521999A_ABST
    Figure CN119521999A_ABST
Patent Text Reader

Abstract

The invention discloses a high-efficiency FAPbI3 perovskite thin film and a preparation method and application thereof, and the method comprises the following steps: S1, dissolving lead iodide and iodoformamidine in a solvent, and obtaining a perovskite precursor solution; s2, under a low-temperature condition, adding a graphene oxide-polyacrylic acid solution into the perovskite precursor solution, and uniformly stirring to obtain an ion recombination perovskite precursor solution; s3, spin-coating the ion recombination perovskite precursor solution on the surface of a conductive substrate with an electron transport layer, and annealing to obtain an active thin film; and S4, sequentially preparing an interface modification layer, a hole transport layer, a metal intercalation layer and a metal electrode layer on the surface of the active thin film to obtain the efficient FAPbI3 perovskite thin film. And the photoelectric property of the FAPbI3 perovskite solar cell can be improved by a method capable of reducing the defects of the perovskite thin film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of optoelectronic technology, and in particular to a high-efficiency FAPbI3 perovskite film and a preparation method and application thereof. Background Art

[0002] Perovskite materials have unique and excellent photovoltaic properties, including high defect tolerance, adjustable band gap, and long exciton diffusion length. Since perovskite materials were used to prepare solar cells, their power conversion efficiency (PCE) has continued to make breakthroughs. The highest PCE of perovskite solar cells (PSCs) has reached 25.7%. Compared with traditional silicon-based solar cells, new perovskite solar cells are easy to prepare and have lower costs. Due to these advantages, perovskite solar cells are becoming more and more prominent. These advantages make perovskite solar cells a popular material for the new generation of solar cells.

[0003] The high perovskite efficiency is mainly due to the amidine-based perovskite, which has a wide absorption wavelength and excellent thermal stability, and has therefore attracted widespread attention in the field of perovskite solar cell research. The crystallinity of the FAPbI3 film prepared by the traditional method and the photovoltaic performance and stability of the prepared device still have room for improvement. The reason is that the surface of the prepared perovskite film is still uneven, the roughness is relatively large, and the crystallinity is not good enough, which is not conducive to the subsequent functional layer deposition. The high defect density in the film is a capture site for carrier transport, which is easy to cause energy loss through non-radiative recombination, resulting in insufficient photovoltaic performance of the device and low energy conversion efficiency.

[0004] Therefore, it is necessary to develop a method to reduce the defects of perovskite films to improve the photoelectric performance of FAPbI3 perovskite solar cells. Summary of the invention

[0005] In view of this, the present application provides a high-efficiency FAPbI3 perovskite film and a preparation method and application thereof, which has high energy conversion efficiency.

[0006] In order to achieve the above technical objectives, this application adopts the following technical solutions:

[0007] In a first aspect, the present application provides a method for preparing a high-efficiency FAPbI3 perovskite film, comprising the following steps:

[0008] S1. dissolving lead iodide and iodomethylamine in a solvent to obtain a perovskite precursor solution;

[0009] S2. Under low temperature conditions, adding graphene oxide-polyacrylic acid solution to the perovskite precursor solution and stirring evenly to obtain an ion-recombined perovskite precursor solution;

[0010] S3. Spin-coating the ion-recombined perovskite precursor solution on the surface of a conductive substrate having an electron transport layer, and annealing to obtain an active film;

[0011] S4. An interface modification layer, a hole transport layer, a metal intercalation layer, and a metal electrode layer are sequentially prepared on the surface of the active film to obtain the high-efficiency FAPbI3 perovskite film.

[0012] Preferably, in step S2, the usage ratio of the perovskite precursor to graphene oxide-polyacrylic acid is 1.5 mmol:5 μg, and the temperature of adding the graphene oxide-polyacrylic acid solution is lower than 4°C.

[0013] Preferably, in step S1, the molar ratio of lead iodide to iodomethylamine is 1:1-2, and the solvent is a mixture of DMF and DMSO.

[0014] Preferably, step S3 includes spin coating the ion recombination perovskite precursor solution on the surface of the conductive substrate having the electron transport layer in batches, adding ether, and annealing at 100-140° C. for 15-20 min, the background material of the electron transport layer is SnO2, and the background material of the conductive substrate is FTO or ITO.

[0015] Preferably, in step S4, the step of preparing the interface modification layer is to spin-coat octyl ammonium iodide on the surface of the active film, and then anneal at 100-120° C. for 1-2 min.

[0016] Preferably, in step S4, the step of preparing the hole transport layer is to spin-coat a mixed solution containing Spiro-OMeTAD on the surface of the interface modification layer, and then oxidize it.

[0017] Preferably, in step S4, the step of preparing the metal intercalation layer is to evaporate MoO3 on the surface of the hole transport layer; in step S4, the step of preparing the metal electrode layer is to evaporate a metal Ag electrode on the surface of the metal intercalation layer.

[0018] Preferably, the mixed solution containing Spiro-OMeTAD comprises a chlorobenzene solution of Spiro-OMeTAD, an acetonitrile solution of lithium bis(trifluoromethanesulfonyl)imide, and TBP.

[0019] In a second aspect, the present application provides a high-efficiency FAPbI3 perovskite film.

[0020] In a third aspect, the present application provides an application of a high-efficiency FAPbI3 perovskite film in the optoelectronic field.

[0021] The beneficial effects of this application are as follows:

[0022] The present application uses graphene oxide-polyacrylic acid as a grain boundary bridging agent, which helps to repair the perovskite film, eliminate cracks, reduce the defects of the perovskite film, and improve the quality of the film; the addition of the grain boundary bridging agent is beneficial to improve the grain boundary flexibility of the perovskite film and passivate the defects of the perovskite film. It has good development prospects and is expected to be used in the preparation of flexible perovskite solar cells in the future;

[0023] The present application improves the quality of the FAPbI3 perovskite film by further controlling the addition amount of the grain boundary bridging agent graphene oxide-polyacrylic acid. The film has excellent crystallinity, is smooth and flat, and has high uniformity, thereby improving the photovoltaic performance of the device and the repeatability of the preparation process, and the energy conversion efficiency can reach 23.66%. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a SEM image of the high-efficiency FAPbI3 perovskite film of Example 1;

[0025] Figure 2 The JV curve of the energy conversion efficiency of the high-efficiency FAPbI3 perovskite film in Example 1;

[0026] Figure 3 Schematic diagram of the structure of the high-efficiency FAPbI3 perovskite film in this scheme. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0028] The present application provides a method for preparing a high-efficiency FAPbI3 perovskite film, comprising the following steps:

[0029] S1. dissolving lead iodide and iodomethylamine in a solvent to obtain a perovskite precursor solution;

[0030] S2. Under low temperature conditions, adding the directly purchased graphene oxide-polyacrylic acid solution to the perovskite precursor solution, stirring evenly, to obtain an ion-recombined perovskite precursor solution;

[0031] S3. Spin-coating the ion-recombined perovskite precursor solution on the surface of a conductive substrate having an electron transport layer, annealing, and obtaining an active film; the active perovskite structure is deposited on the surface of the conductive substrate having an electron transport layer;

[0032] S4. An interface modification layer, a hole transport layer, a metal intercalation layer, and a metal electrode layer are sequentially prepared on the surface of the active film to obtain the high-efficiency FAPbI3 perovskite film.

[0033] In the present application, graphene oxide-polyacrylic acid is added to the perovskite precursor solution as a grain boundary bridge agent to bridge the grain boundaries of the perovskite, fill the perovskite grain boundaries, and assist the growth of the perovskite film. The obtained perovskite active film has high flatness, high fineness, and good crystallinity, which is conducive to the deposition of subsequent functional layers. The perovskite device prepared based on this perovskite film also has more excellent photovoltaic performance.

[0034] In step S1, the molar ratio of lead iodide to iodomethylamine is 1:1-2, and the solvent is a mixture of DMF and DMSO.

[0035] In step S2, the dosage ratio of the perovskite precursor to graphene oxide-polyacrylic acid is 1.5mmol:5μg; the temperature for adding the graphene oxide-polyacrylic acid solution is lower than 4°C; at this dosage ratio, the photovoltaic performance is better; specifically, the perovskite precursor solution obtained in step S1 is stirred at low temperature for 4-6h, and after it is completely dissolved, graphene oxide-polyacrylic acid (GO-PAA) is added, and stirring is continued for 6h to perform ion recombination and construct a pre-perovskite structure to obtain an ion-recombined perovskite precursor solution.

[0036] Step S3 comprises, in a nitrogen glove box without water and oxygen, spin coating the ion recombination perovskite precursor solution on the surface of the conductive substrate having the electron transport layer in batches, adding ether dropwise, and annealing at 100-140° C. for 15-20 min, wherein the background material of the electron transport layer is SnO2, and the background material of the conductive substrate is FTO or ITO;

[0037] The preparation method of a conductive substrate with an electron transport layer includes: cleaning the conductive substrate and treating it with an ultraviolet ozone cleaning agent, dripping a SnO2 solution onto the treated conductive substrate, spin coating it into a film, spin coating it at a speed of 4000 rpm for 30 seconds, and then annealing it at 150°C for 30 minutes to obtain a conductive substrate with an electron transport layer.

[0038] The specific operation of step S3 is as follows: in a nitrogen glove box without water and oxygen, a conductive substrate with an electron transport layer is placed on a spin coating apparatus, and the ion recombination perovskite precursor solution obtained in step S2 is dripped on its surface, and the two-step spin coating method is used for spin coating, first at 1000 rpm for 10 seconds, then at 5000 rpm for 30 seconds, and at the countdown of 20 seconds, 800 μl of ether is dripped, and after spin coating, annealing is performed at 140-150° C. on a hot stage for 15-20 minutes to obtain a dense and uniform active film. In this step, the anti-solvent ether is spin-coated, and the transformation of the black phase perovskite can be achieved at high temperature.

[0039] In step S4, the step of preparing the interface modification layer is to spin-coat the octyl ammonium iodide solution on the surface of the active film at a speed of 4000 rpm, and then anneal at 100-120° C. for 1-2 min; the concentration of the octyl ammonium iodide solution is 5 mg / ml.

[0040] In step S4, the step of preparing the hole transport layer is to spin-coat the mixed solution containing Spiro-OMeTAD on the surface of the interface modification layer at a speed of 2500 rpm, and then oxidize the coated film in an air glove box for 20 hours.

[0041] The specific steps for preparing the hole transport layer are as follows: (1) dissolving 73.2 mg of Spiro-OMeTAD in 1 mL of chlorobenzene; (2) dissolving 520 mg of lithium bis(trifluoromethanesulfonyl)imide in 1 mL of acetonitrile solution to prepare a lithium salt solution; (3) adding 28.8 μL of TBP solution to the Spiro-OMeTAD solution; (4) taking 17.6 μL of lithium salt solution to dope the Spiro-OMeTAD solution; (5) stirring the mixed solution of (1)-(4) at room temperature for 2 h; and (6) the spin coating condition is 2500 rpm for 30 s.

[0042] In step S4, the step of preparing the metal intercalation layer is to vacuum-deposit MoO3 on the surface of the hole transport layer at a rate of 0.2 angstroms / second to obtain a metal intercalation layer with a thickness of 220 angstroms; in step S4, the step of preparing the metal electrode layer is to vacuum-deposit a metal Ag electrode on the surface of the metal intercalation layer at a rate of 2 angstroms / second to a thickness of 2000 angstroms.

[0043] The mixed solution containing Spiro-OMeTAD comprises a chlorobenzene solution of Spiro-OMeTAD, an acetonitrile solution of lithium bis(trifluoromethanesulfonyl)imide, and TBP.

[0044] like Figure 3 As shown, the present application provides a high-efficiency FAPbI3 perovskite film, which is provided with a metal electrode layer, a metal intercalation layer, a hole transport layer, an active perovskite layer, an electron transport layer, and a conductive substrate in sequence from top to bottom; the high-efficiency FAPbI3 perovskite film obtained has an open circuit voltage of 1.12V and a short circuit current of 25.50mA / cm 2 , the filling factor is 82.53%, and the energy conversion efficiency is 23.66%.

[0045] The present application provides an application of a high-efficiency FAPbI3 perovskite film in the optoelectronic field.

[0046] The present solution is further described below through specific implementation methods.

[0047] Example 1

[0048] A method for preparing a high-efficiency FAPbI3 perovskite film comprises the following steps:

[0049] S1. Weigh 0.8190 g of lead iodide (due to the use of weighing paper, lead iodide will remain on the paper, so the actual weighed amount is slightly more than the calculated amount), 0.2648 g of formamidine iodide, and 0.03713 g of methylamine chloride in a molar ratio of 1:1, and dissolve them in 1000 μL of a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide (volume ratio of 890 μL:110 μL), and stir on a cold table for 4-6 hours to completely dissolve them to obtain a perovskite precursor solution;

[0050] S2. 1 ml of the 1.5 mmol / ml perovskite precursor solution obtained by filtering step S1 was added with 10 μL of 0.5 mg / ml GO-PAA and stirred for 6 h (the ratio of the perovskite precursor to graphene oxide-polyacrylic acid was 1.5 mmol: 5 μg) to prepare an ion-recombined perovskite precursor solution;

[0051] S3. Soak the etched FTO conductive glass with a size of 1.2×1.2cm in ethanol, ultrapure water with detergent, ultrapure water, and ethanol for 30 minutes each, then blow dry with a nitrogen gun and store it; treat the cleaned FTO substrate with a UV ozone cleaner for 20 minutes; take 40μL of diluted SnO2 (mix and dissolve SnO2 solution and deionized water in a ratio of 1:5) solution and drop it on the treated FTO substrate, spin coat it at 4000rpm for 30s, and then anneal it at 150℃ for 30 minutes to obtain a film with A conductive substrate with an electron transport layer is then treated with an ozone cleaner for 20 minutes; the ion recombination perovskite precursor solution is filtered using an organic filter membrane, the conductive substrate with an electron transport layer is placed on a spin coating instrument, 45 μL of the ion recombination perovskite precursor solution is dripped on it, and a two-step spin coating method is used for spin coating. The specific experimental operation is: first spin coating at a speed of 1000 rpm for 10 seconds, then spin coating at a speed of 5000 rpm for 30 seconds, and in the remaining 20 seconds, 800 μL of ether is dripped, and after spin coating, annealing at 140° C. for 15 minutes to obtain an active film;

[0052] S4. Spin-coat an octylamine iodide (OAI) interface layer on the surface of the active film in step S3. The specific operation is as follows: add 40 μL of 5 mg / ml OAI solution to the active film, then spin-coat at 4000 rpm for 30 seconds, and then anneal at 100°C for 1 minute to obtain an interface modification layer; add 50 μL of Spiro-OMeTAD mixed solution to the interface modification layer, then spin-coat at 2500 rpm / s for 30 seconds, and oxidize the coated film in an air glove box for 20 hours to obtain a hole transport layer; vacuum-deposit a metal intercalation layer and a metal electrode on the surface of the hole transport layer. The specific operation is as follows: first, evaporate MoO3 at a rate of 0.2 angstroms / second on the hole transport layer to a thickness of 220 angstroms; then evaporate a metal Ag electrode at a rate of 2 angstroms / second on the MoO3 to a thickness of 2000 angstroms to obtain a high-efficiency FAPbI3 perovskite film. SEM pictures are shown in the figure below. Figure 1 shown.

[0053] Figure 2 The JV curve of the energy conversion efficiency of the high-efficiency FAPbI3 perovskite film in Example 1; under standard test conditions (AM1.5G illumination, direct test using a solar simulator), the open circuit voltage of the optimal battery device prepared in this example is 1.12V, and the short circuit current is 25.50mA / cm 2 , the filling factor is 82.53% and the energy conversion efficiency is 23.66%.

[0054] Example 2

[0055] A method for preparing an efficient FAPbI3 perovskite film, the other contents are the same as those in Example 1, except that 9 μL GO-PAA at 0.5 mg / ml is added in step S2.

[0056] Under standard test conditions (AM1.5G illumination, direct testing using a solar simulator Enli Tech, Taiwan), the optimal cell device prepared in this example has an open circuit voltage of 1.12V and a short circuit current of 25.61mA / cm 2 , the filling factor is 81.34% and the energy conversion efficiency is 23.25%.

[0057] Example 3

[0058] A method for preparing an efficient FAPbI3 perovskite film, the other contents are the same as those of Example 1, except that 11 μL GO-PAA at 0.5 mg / ml is added in step S2.

[0059] Under standard test conditions (AM1.5G illumination), the optimal battery device prepared in this example has an open circuit voltage of 1.12 and a short circuit current of 25.73 mA / cm 2, filling factor 79.72, energy conversion efficiency 22.98%.

[0060] Comparative Example 1

[0061] A method for preparing a high-efficiency FAPbI3 perovskite film, other contents are the same as those of Example 1, except that step S2 is not included.

[0062] From the above results, it can be seen that the graphene oxide-polyacrylic acid added to the perovskite precursor solution is distributed at the perovskite grain boundaries, can bridge the grain boundaries, fill the perovskite grain boundaries, assist the perovskite crystallization, increase the flexibility of the grain boundaries, and make the perovskite film have fewer defects. With the increase in the amount of GO-PAA added, the photovoltaic performance, energy conversion efficiency and filling factor of the device show a trend of first increasing and then decreasing. Examples 2 and 3 confirm this point. If the amount added is too little, the bridging is not completely completed, and the photovoltaic performance is not high. If too much is added, the bridging is excessive, and there is excess GO-PAA dispersion, resulting in a reduction in the amount of photogenerated carriers generated, affecting the device performance. The amount added in Example 1 is optimal, and the device with the best performance can be prepared.

[0063] Figure 1 The SEM images of the high-efficiency FAPbI3 perovskite film of Example 1 and the perovskite film without GO-PAA added (Comparative Example 1, the energy conversion efficiency tested under the same conditions is less than 22%) show that during the annealing process of the perovskite film, it can be found that some tiny cracks generated during the spin coating process disappeared after annealing, which also shows that the addition of graphene oxide-polyacrylic acid helps to repair the perovskite film and improve the quality of the film.

[0064] By comparing the amount of graphene oxide-polyacrylic acid added as the grain boundary bridging agent in Examples 1-3, the quality of the FAPbI3 perovskite film can be further improved, while the photovoltaic performance of the device and the repeatability of the preparation process are improved. With the increase in the amount of GO-PAA added, the photovoltaic performance of the device shows a trend of first increasing and then decreasing. Since the amount of graphene oxide-polyacrylic acid added in Example 1 is appropriate, the quality of the prepared perovskite film has the advantages of crystallinity and smoother film, and the photovoltaic performance of the prepared device is higher than that of the control. Although the photovoltaic performance of the FAPbI3 perovskite solar cell prepared in Example 3 is worse than that in Example 1, when the film thickness is already uneven and the quality is poor, there is still an efficiency of more than 22%, which also confirms that the appropriate amount of graphene oxide-polyacrylic acid has the advantage of improving the quality of the perovskite film, which is conducive to the preparation of a perovskite film with fewer defects. The addition of the grain boundary bridging agent in this application is conducive to improving the grain boundary flexibility of the perovskite film, has good development prospects, and is expected to be used in the preparation of flexible perovskite solar cells in the future. When the added amount is appropriate, the microscopic morphology of the perovskite film has better uniformity and better crystallinity. In Example 1, the addition amount of the grain boundary bridging agent graphene oxide-polyacrylic acid is 10 μL at a concentration of 0.5 mg / ml, which is the best.

[0065] The above are only preferred specific implementations of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A method for preparing an efficient FAPbI3 perovskite film, characterized in that: The following steps are involved: S1. dissolving lead iodide and iodomethylamine in a solvent to obtain a perovskite precursor solution; S2. Adding graphene oxide-polyacrylic acid solution to the perovskite precursor solution and stirring evenly to obtain an ion-recombined perovskite precursor solution; S3. Spin-coating the ion-recombined perovskite precursor solution on the surface of a conductive substrate having an electron transport layer, and annealing to obtain an active film; S4. An interface modification layer, a hole transport layer, a metal intercalation layer, and a metal electrode layer are sequentially prepared on the surface of the active film to obtain the high-efficiency FAPbI3 perovskite film.

2. The method for preparing a high-efficiency FAPbI3 perovskite film according to claim 1, characterized in that: In step S2, the usage ratio of the perovskite precursor to graphene oxide-polyacrylic acid is 1.5 mmol:5 μg, and the temperature of adding the graphene oxide-polyacrylic acid solution is lower than 4°C.

3. The method for preparing a high-efficiency FAPbI3 perovskite film according to claim 1, characterized in that: In step S1, the molar ratio of lead iodide to iodomethylamine is 1:1-2, and the solvent is a mixture of DMF and DMSO.

4. The method for preparing a high-efficiency FAPbI3 perovskite film according to claim 1, characterized in that: Step S3 includes spin coating the ion recombination perovskite precursor solution on the surface of the conductive substrate having the electron transport layer in batches, adding ether, and annealing at 100-140° C. for 15-20 min, wherein the background material of the electron transport layer is SnO2, and the background material of the conductive substrate is FTO or ITO.

5. The method for preparing a high-efficiency FAPbI3 perovskite film according to claim 1, characterized in that: In step S4, the step of preparing the interface modification layer is to spin-coat octyl ammonium iodide on the surface of the active film, and then anneal at 100-120° C. for 1-2 minutes.

6. The method for preparing a high-efficiency FAPbI3 perovskite film according to claim 1, characterized in that: In step S4, the step of preparing the hole transport layer is to spin-coat a mixed solution containing Spiro-OMeTAD on the surface of the interface modification layer, and then oxidize it.

7. The method for preparing a high-efficiency FAPbI3 perovskite film according to claim 1, characterized in that: In step S4, the step of preparing the metal intercalation layer is to evaporate MoO3 on the surface of the hole transport layer; in step S4, the step of preparing the metal electrode layer is to evaporate a metal Ag electrode on the surface of the metal intercalation layer.

8. The method for preparing a high-efficiency FAPbI3 perovskite film according to claim 6, characterized in that: The mixed solution containing Spiro-OMeTAD comprises a chlorobenzene solution of Spiro-OMeTAD, an acetonitrile solution of lithium bis(trifluoromethanesulfonyl)imide, and TBP.

9. A high-efficiency FAPbI3 perovskite film obtained by the preparation method according to any one of claims 1 to 8.

10. Application of the high-efficiency FAPbI3 perovskite film as claimed in claim 9 in the field of optoelectronics.